Ratio fluorescent magnetic composite material as well as preparation method and application thereof

Through the use of ratio fluorescent magnetic Ni-EFMMS@nNOS-PSD95 composite materials, the problem of insufficient complexity and sensitivity of screening nNOS-PSD95 uncoupling agents in the prior art is solved, and the nNOS-PSD95 uncoupling in natural medicines is achieved The rapid and efficient screening of coupling agents provides a new method for screening active ingredients against stroke.

CN119307486APending Publication Date: 2025-01-14NANJING MEDICAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411419256.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The prior art has problems such as complex methods, high cost, insufficient sensitivity and high false positive rate when screening nNOS-PSD95 uncoupling agents in natural drugs, making it difficult to achieve efficient screening and accurate analysis.

Method used

Using ratio fluorescent magnetic Ni-EFMMS@nNOS-PSD95 composite material, His-nNOS and GFP-PSD95 are fixed by epoxy functionalized fluorescent magnetic mesoporous silicon carrier, combining magnetic separation and fluorescence analysis to achieve rapid and efficient screening of natural drugs. nNOS-PSD95 uncoupling agent.

Benefits of technology

The rapid and accurate screening of nNOS-PSD95 uncoupling agent in natural drugs is achieved, which reduces experimental costs and operational complexity, improves screening efficiency and accuracy, and provides a new method for screening anti-stroke active ingredient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307486A_ABST
    Figure CN119307486A_ABST
Patent Text Reader

Abstract

The invention discloses a ratio fluorescent magnetic composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: (1) preparation of silanized carbon dots, (2) preparation of epoxy functionalized fluorescent magnetic mesoporous silicon, (3) preparation of a multifunctional epoxy carrier Ni-EFMMS, (4) preparation of Ni-EFMMS (at) nNOS, and (5) preparation of a Ni-EFMMS (at) nNOS-PSD95 composite material. According to the Ni-EFMMS-nNOS-PSD95 ratiometric fluorescent magnetic composite material based on magnetic mesoporous silica, the convenience of magnetic separation, the high specific surface area of the mesoporous silica material and the high stability of ratiometric fluorescent detection are combined, and PSD95-nNOS uncoupling agent active substances can be quickly and efficiently found; a new thought and a new method are provided for screening candidate drugs for resisting cerebral arterial thrombosis in natural drugs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of natural medicine and materials science, and specifically relates to a fluorescent magnetic Ni-EFMMS@nNOS-PSD95 composite material and a preparation method thereof, as well as an application in screening potential anti-stroke active ingredients of natural medicines. Background Art

[0002] Stroke is an important cause of death. Due to its high disability rate, it seriously affects the daily life of survivors. Cerebral ischemia leads to excessive activation of N-methyl-D-aspartate receptors (NMDARs), which in turn induces neuronal nitric oxide synthase (nNOS) to bind to postsynaptic density protein 95 (PSD95), catalyzing the production of a large amount of nitric oxide (NO), which reacts with oxygen free radicals O2 - Reaction to form highly toxic nitrite anion free radical ONOO - , which leads to neuronal death. Small molecule inhibitors, such as 4-(2-hydroxy-3,5-dichlorobenzylamino)-2-hydroxybenzoic acid (ZL006), can selectively block PSD95-nNOS binding and improve focal cerebral ischemic injury. However, due to the poor blood-brain barrier (BBB) ​​permeability of ZL006, the therapeutic effect on ischemic stroke is still unsatisfactory, so further research on new PSD95-nNOS uncouplers is needed.

[0003] A large number of studies have shown that some natural active ingredients have the effects of inhibiting cell apoptosis, oxidative stress and inflammatory response, and promoting angiogenesis and neurogenesis. They can be used for targeted treatment of ischemic stroke and have fewer side effects, such as puerarin and berberine. Regarding the research on nNOS-PSD95 uncouplers, the traditional methods are mainly yeast two-hybrid, immunoprecipitation and pull-down. Most of these methods require antibodies to capture the target protein, Western blot or mass spectrometry for analysis, strict experimental conditions, complex operations, high prices, and are not suitable for large-scale screening. Patents 201910699052.5, 201710474093.5, and 201710474123.2 constructed a method for in vitro screening of PSD95-nNOS uncouplers based on molecular imprinting technology, but they must rely on known template molecules with uncoupling effects. The structural diversity of the compounds is severely limited, and the evaluation of uncoupling activity still requires the traditional pull-down method. 202111346568.5 Taking advantage of the high sensitivity and convenience of fluorescence analysis, a method for efficiently screening PSD95-nNOS uncouplers was constructed. However, in this method, nNOS and the material are bound by a coordination bond. The target protein is easily detached during screening, resulting in false positives. At the same time, single fluorescence analysis is easily interfered by external factors and the analysis is inaccurate. Summary of the invention

[0004] In order to solve the above-mentioned technical problems existing in the prior art, the present invention provides a ratiometric fluorescent magnetic Ni-EFMMS@nNOS-PSD95 composite material and a preparation method thereof, specifically, a method for quickly and efficiently screening nNOS-PSD95 uncouplers from natural medicines, laying a foundation for finding anti-stroke candidate drugs with significant activity, and providing a new method and new strategy for screening natural medicine uncoupling active ingredients.

[0005] The technical solution of the present invention is as follows:

[0006] A ratio fluorescent magnetic composite material comprises epoxy functionalized fluorescent magnetic mesoporous silicon, metal ions, His-nNOS and GFP-PSD95. The ratio fluorescent magnetic composite material uses epoxy functionalized fluorescent magnetic mesoporous silicon as a carrier, carries metal ions, fixes His-nNOS on the surface of the material, and combines GFP-PSD95 with the His-nNOS on the surface to fix the ratio fluorescent magnetic composite material.

[0007] The His-nNOS refers to neuronal nitric oxide synthase (nNOS) carrying a His tag, and the GFP-PSD95 refers to postsynaptic density protein 95 (PSD95) combined with a GFP fluorescent marker.

[0008] Further, the metal ion is selected from iron, cobalt, copper, nickel or zinc;

[0009] Furthermore, the mass ratio of epoxy-functionalized fluorescent magnetic mesoporous silica, metal ions, His-nNOS and GFP-PSD95 was 10:0.09:1:1.

[0010] The method for preparing the aforementioned ratio fluorescent magnetic composite material comprises the following steps:

[0011] (1) Preparation of silylated carbon dots: citric acid and urea are added to formic acid to perform solvent thermal treatment, and the solvent thermal treatment product is precipitated by ethanol to obtain red carbon dots; the red carbon dots are dispersed in dimethyl sulfoxide, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide are added for activation, and 3-aminopropyltriethoxysilane is added, and the mixture is shaken at room temperature to obtain the silylated carbon dots;

[0012] (2) Preparation of epoxy-functionalized fluorescent magnetic mesoporous silica: Fe3O4 magnetic nanoparticles were acoustically dispersed in an 80% ethanol aqueous solution, ammonia water was added, tetraethyl orthosilicate was slowly added dropwise after stirring evenly, and the suspension was reacted at room temperature until the color of the suspension became lighter, gradually changing from black to brown. The product was magnetically separated and washed with deionized water until neutral to obtain Fe3O4@nSiO2; Fe3O4@nSiO2 was redispersed in a mixed solvent of water, ethanol and ammonia water, and a template was added to react at room temperature until the template was evenly dispersed in the mixed solvent; step ( 1) The obtained silanized carbon dots are added with tetraethyl orthosilicate for the second time, and the silanized carbon dots and tetraethyl orthosilicate are co-condensed on the surface of Fe3O4@nSiO2 to form fluorescent (fluorescence originates from the silanized carbon dots) magnetic mesoporous silicon, and mechanical stirring is performed until the silanized carbon dots and tetraethyl orthosilicate are condensed to form a mesoporous silicon layer, and 3-glycidyloxypropyltrimethoxysilane is added for epoxy functionalization, and the reaction is continued to be stirred, and the product is dispersed in acetone, refluxed, and repeated twice, and the product is magnetically collected and vacuum dried to constant weight to obtain epoxy-functionalized fluorescent magnetic mesoporous silicon;

[0013] (3) Preparation of multifunctional epoxy carrier Ni-EFMMS: Mix the epoxy-functionalized fluorescent magnetic mesoporous silica obtained in step (2) with water or an aqueous solution of iminodiacetic acid, and react at room temperature until the iminodiacetic acid fully reacts with the epoxy group; after washing with deionized water, collect the product and continue to react with an excess metal ion solution at room temperature until the carboxyl group fully chelates the metal ion; after washing with deionized water, collect the product magnetically, and vacuum dry it to constant weight to obtain a multifunctional epoxy carrier (e.g., Ni-EFMMS);

[0014] (4) Preparation of nNOS-fixed epoxy-functionalized fluorescent magnetic mesoporous silica: The multifunctional epoxy carrier prepared in step (3) is uniformly dispersed in a His-nNOS protein solution, fixed at room temperature, and then magnetically separated. The separated material is incubated in an imidazole solution and a glycine solution in turn, and then magnetically separated to obtain the epoxy-functionalized fluorescent magnetic mesoporous silica (e.g., Ni-EFMMS@nNOS);

[0015] (5) Preparation of ratiometric fluorescent magnetic composite material: The nNOS-fixed epoxy-functionalized fluorescent magnetic mesoporous silica prepared in step (4) is uniformly dispersed in the GFP-PSD95 protein solution, incubated, and magnetically separated to obtain the ratiometric fluorescent magnetic composite material (e.g., Ni-EFMMS@nNOS).

[0016] Furthermore, in step (1), the mass ratio of citric acid to urea is 1:1 to 1:3, and the concentration of citric acid in formic acid is 0.1 g / mL; the conditions for the solvent thermal treatment are 160° C., 4 h; the molar ratio of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride to N-hydroxysuccinimide is 1:1 to 1:2, and the molar ratio of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride to 3-aminopropyltriethoxysilane is 1:0.1 to 1:0.3.

[0017] Furthermore, in step (2), the concentration of the Fe3O4 magnetic nanoparticles in the 80% ethanol aqueous solution is 1 mg / mL, the volume ratio of the 80% ethanol aqueous solution to ammonia water is 100:1, and the volume ratio of tetraethyl orthosilicate to ammonia water is 1:10; the volume ratio of water, ethanol and ammonia water in the mixed solvent is 80:60:1, and the concentration of the Fe3O4@nSiO2 in the mixed solvent is 0.5-1 g / mL; the template is hexadecyltrimethylammonium bromide, and the mass ratio of Fe3O4@nSiO2 to the template is 1:3-1:5; the mass ratio of the silanized carbon dots to tetraethyl orthosilicate is 1:60-1:90; the mechanical stirring condition is 750 r / min; the molar ratio of the tetraethyl orthosilicate added for the second time as the silicon source and the 3-glycidyloxypropyltrimethoxysilane for epoxy functionalization is 2:1-6:1.

[0018] The preparation method of the Fe3O4 magnetic nanoparticles in step (2) is as follows: 60-100 mL of ultrapure water is added to a reaction container in proportion, 5-20 mmol of FeCl2·4H2O and 10-40 mmol of FeCl3·6H2O are added under nitrogen protection, 5-20 mL of ammonia water is added dropwise when the oil bath is heated to 60-120° C., the reaction is continued for 0.5-2 h, and then 1-4 mL of polyethylene glycol 200 is added under stirring and the reaction is carried out for 5-20 min. The reaction is protected by nitrogen throughout the process, the product is magnetically separated, and washed with deionized water until neutral to obtain Fe3O4 nanoparticles, which are then vacuum dried at 50° C. for later use.

[0019] Furthermore, in step (3), the concentration of the epoxy-functionalized fluorescent magnetic mesoporous silica in diacidic acid is 0.01 g / mL; the concentration of the diacidic acid aqueous solution is not higher than 50 mM; the metal ions are iron, cobalt, copper, nickel or zinc; and the vacuum drying temperature is 45°C.

[0020] Furthermore, in step (4), the mass ratio of the multifunctional epoxy carrier to His-nNOS is 20:1 to 1:1, and the fixation time at room temperature is 12 to 36 hours; the concentrations of the imidazole solution and the glycine solution are both 0.5 M; and the incubation condition is 4° C. for 2 hours.

[0021] In a specific embodiment, the concentration of the separated material in the imidazole solution and the glycine solution is consistent with that in the His-nNOS protein solution.

[0022] Furthermore, the incubation conditions in step (5) are 4° C. and 175 rpm for 12 h, and the mass ratio of nNOS and PSD95 used in protein fixation is 0.5:1 to 2:1.

[0023] Application of the aforementioned ratiometric fluorescent magnetic composite material in screening potential anti-stroke active ingredients of natural medicines.

[0024] Furthermore, the ratio fluorescence magnetic composite material is added to the natural medicine to be screened or the solution of the active ingredient of the natural medicine, shaken and magnetically separated, and the ratio fluorescence intensity of the ratio fluorescence magnetic composite material is measured, so as to compare and screen out the active ingredients of the natural medicine that meet the conditions.

[0025] Furthermore, the shaking condition was 125 rpm at 4°C for 5 h.

[0026] Magnetic mesoporous silica (MMS) can use the effect of magnetic field to achieve rapid separation and increase the recovery rate of materials; and magnetic mesoporous silica has a surface that is easy to be epoxy-functionalized and a large specific surface area, and has good biocompatibility and stability. Studies have shown that the multifunctional epoxy carrier synthesized by partially functionalizing the epoxy groups on the carrier surface with metal ions can take into account the protein purification ability of the His tag and the covalent fixation ability of the epoxy groups, achieving the simultaneous purification and immobilization of His-nNOS, which is more conducive to the construction of a stable and reliable screening system. Silanized carbon dots are silanized carbon dots, so that they can be functionalized on the surface of magnetic mesoporous silica to make them have carbon dot fluorescence. In this paper, the fluorescence of carbon dots is combined with the fluorescence of GFP-PSD95 to form a ratio fluorescence for the screening of nNOS-PSD95 uncouplers. At present, the use of Ni-EFMMS@nNOS-PSD95 composite materials to discover nNOS-PSD95 uncouplers in natural medicines has not been reported.

[0027] Beneficial effects:

[0028] The invention combines fluorescent carbon dots and magnetic mesoporous silica, integrating the advantages of selective adsorption of histidine tags and covalent fixation of proteins by epoxy groups, and designs and synthesizes a ratiometric fluorescent magnetic composite material for simultaneous purification and covalent fixation of proteins. It is then used to screen potential nNOS-PSD95 uncoupling active substances in natural active ingredients.

[0029] The excellent effects of the present invention are mainly manifested in:

[0030] 1. The ratiometric fluorescent magnetic composite material (eg, Ni-EFMMS@nNOS-PSD95 composite material) synthesized by the present invention can be dispersed and then re-aggregated within 30 seconds in an external magnetic field, thereby achieving simple and rapid separation of protein-fixed materials.

[0031] 2. The present invention synthesizes an epoxy functionalized surface and partially chelates metal ions thereon. The metal ions can selectively adsorb His-nNOS and promote its covalent fixation with epoxy groups, thereby achieving simultaneous purification and covalent fixation of His-nNOS.

[0032] 3. The present invention silanizes red carbon dots and assembles them inside magnetic mesoporous silica as internal reference fluorescence, which forms ratio fluorescence with green fluorescent protein labeled on PSD95, without the need for template molecules. The ratio fluorescence intensity change of the material is used to discover potential nNOS-PSD95 uncouplers from natural active ingredients.

[0033] The present invention utilizes the advantages of magnetic mesoporous silica, such as good stability, large specific surface area, easy separation, and easy structural modification, and uses it as a carrier to simultaneously purify and covalently fix His-nNOS protein in one step by adjacent connection. At the same time, it is combined with the high sensitivity, rapid detection, and anti-interference of ratiometric fluorescence analysis to prepare a ratiometric fluorescent magnetic composite nanoprobe, which can achieve rapid discovery of PSD95-nNOS uncouplers in complex environments, laying a foundation for the discovery of new anti-stroke active substances. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The scanning electron microscope image and transmission electron microscope image of Ni-EFMMS@nNOS-PSD95 prepared in Example 1; (A is a scanning electron microscope image of Ni-EFMMS@nNOS-PSD95, and B is a transmission electron microscope image of Ni-EFMMS@nNOS-PSD95)

[0035] Figure 2 The iminodiacetic acid concentration and metal ion type optimization of Ni-EFMMS@nNOS-PSD95 prepared in Example 1. (A is the effect of iminodiacetic acid concentration on Ni-EFMMS fixation of His-nNOS, and B is the effect of metal ion type on Ni-EFMMS fixation of His-nNOS.)

[0036] Figure 3 The hysteresis loop of the Ni-EFMMS@nNOS-PSD95 composite material prepared in Example 1 (the magnetization intensity from high to low is Fe3O4, Fe3O4@nSiO2, epoxy functionalized fluorescent magnetic mesoporous silicon, Ni-EFMMS, Ni-EFMMS@nNOS and Ni-EFMMS@nNOS-PSD95)

[0037] Figure 4 is the linear relationship of Ni-EFMMS@nNOS-PSD95 prepared in Example 1 under the action of different concentrations of uncoupler ZL006. (A is F 506 / F 632 A is the linear relationship between the decoupling efficiency and the ZL006 concentration, and B is the linear relationship between the decoupling efficiency and the ZL006 concentration.

[0038] Figure 5 It is the covalent protein loading rate of the multifunctional epoxy carrier prepared in Example 1 to His-nNOS. DETAILED DESCRIPTION

[0039] The present invention is further explained below with reference to the examples, but the examples do not limit the present invention in any form.

[0040] Example 1

[0041] Preparation of materials:

[0042] (1) Preparation of silanized carbon dots: According to the proportion, 1 g of citric acid and 2 g of urea were added to 10 mL of formic acid and subjected to solvent thermal treatment at 160 °C for 4 h. The 10 ml dark red-brown solution obtained after solvent thermal treatment was precipitated with ethanol to obtain red carbon dots. It was dispersed in 2 mL of dimethyl sulfoxide, and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide were added for activation for 30 min, and then 5 μL of 3-aminopropyltriethoxysilane was added and shaken at room temperature for 12 h to obtain silanized carbon dots, which were stored at 4 °C for future use;

[0043] (2) Preparation of epoxy-functionalized fluorescent magnetic mesoporous silica: 60-100 mL of ultrapure water were added to the reaction vessel in proportion, and 5-20 mmol of FeCl2·4H2O and 10-40 mmol of FeCl3·6H2O were added under nitrogen protection. When the oil bath was heated to 60-120°C, 5-20 mL of ammonia water was added dropwise, and the reaction was continued for 0.5-2 h. Then, 1-4 mL of polyethylene glycol 200 was added under stirring and the reaction was continued for 5-20 min. Nitrogen was used for protection throughout the reaction. The product was magnetically separated and washed with deionized water until neutral to obtain Fe3O4 nanoparticles, which were vacuum dried at 50°C and set aside. 0.1 g of the obtained Fe3O4 was ultrasonically dispersed in a mixed solution of 80 mL of ethanol and 20 mL of deionized water, and 1 mL of ammonia water was added. After stirring, 100 μL of tetraethyl orthosilicate was slowly added dropwise. The reaction was continued at room temperature for 6 h. The product was magnetically separated and washed with deionized water until neutral to obtain Fe3O4@nSiO2. Re-disperse Fe3O4@nSiO2 in a mixed solvent of 80mL deionized water, 60mL ethanol, and 1mL ammonia water, add the template agent hexadecyltrimethylammonium bromide and react at room temperature for 30 minutes, then add the above-obtained silanized carbon dots and 400μL tetraethyl orthosilicate, and the two are co-condensed to form fluorescent magnetic mesoporous silica, and mechanically stirred at a speed of 750r / min for 2h, and then add 100μL 3-glycidyloxypropyltrimethoxysilane for epoxy functionalization, and continue to stir and react for 2h. The product is dispersed in acetone, refluxed at 80℃ for 2d, repeated twice, the product is magnetically collected, and vacuum dried at 45℃ to constant weight to obtain epoxy-functionalized fluorescent magnetic mesoporous silica;

[0044] (3) Preparation of multifunctional epoxy support Ni-EFMMS: 0.1 g epoxy functionalized fluorescent magnetic mesoporous silica was mixed with 10 mL 0.5 mM iminodiacetic acid aqueous solution and reacted at room temperature for 1 h. After washing with deionized water, the product was collected and continued to react with excess Ni 2+ The solution was reacted at room temperature for 2 h, and the product was collected magnetically after washing with deionized water and dried in vacuo at 45 °C to constant weight to obtain Ni-EFMMS;

[0045] (4) Preparation of Ni-EFMMS@nNOS: 3 mg of the above Ni-EFMMS was uniformly dispersed in 300 μL of His-nNOS protein solution (1 mg / mL), fixed at room temperature for 24 h, and then magnetically separated. The material was uniformly dispersed in 300 μL of imidazole solution and glycine solution (both 0.5 M), and incubated at 4°C for 2 h, respectively, and then magnetically separated.

[0046] (5) Preparation of Ni-EFMMS@nNOS-PSD95 composite material: 3 mg Ni-EFMMS@nNOS was evenly dispersed in 300 μL GFP-PSD95 (1 mg / mL) protein solution, incubated at 4°C, 175 rpm for 12 h, and magnetically separated to obtain the composite material.

[0047] The scanning electron microscopy and transmission electron microscopy images of Ni-EFMMS@nNOS-PSD95 are shown in Figure 1 The results show that the synthesized Ni-EFMMS@nNOS-PSD95 has a uniform morphology and a particle size of about 250 nm. Figure 1 The scanning electron microscopy image of A shows that the surface of the material is rough, which is attributed to the successful fixation of the protein on the surface of the material. Figure 1 B Transmission electron microscopy image proves that it has a layered structure with Fe3O4 as the core and covered with a mesoporous silicon layer, indicating that the material structure is not destroyed after the fixation of His-nNOS and GFP-PSD95, proving the stability of Ni-EFMMS.

[0048] The optimization process of iminodiacetic acid concentration and metal ion type is as follows: 100 mg of epoxy-functionalized fluorescent magnetic mesoporous silica is uniformly dispersed in 10 mL of iminodiacetic acid aqueous solution (IDA aqueous solution) of different concentrations (0 mM, 0.05 mM, 0.5 mM, 5 mM, 50 mM, pH 8), reacted at room temperature for 1 hour, and the product was recovered by magnetic separation. After washing with deionized water, it was redispersed in 10 mL of NiSO4·6H2O (0.5 M) solution, reacted at room temperature for 2 hours, washed with deionized water, and vacuum dried. Weigh 3 mg of Ni-EFMMS obtained by the above-mentioned IDA treatment with different concentrations, fix His-nNOS according to the above steps, and calculate the covalent protein loading rate of Ni-EFMMS at different IDA concentrations according to formula (1). Similarly, the optimization process of metal ion type is as follows: 100 mg of synthesized IDA-EFMMS is mixed with 10 mL of 0.5 M Fe 3+ 、Co 2+ , Cu 2+ 、Ni 2+ 、Zn 2+ The reaction was carried out at room temperature for 2 h, and the product was collected by magnetic separation after washing with deionized water. His-nNOS was fixed according to the above steps, and the covalent protein loading rate of the material after chelation with different metal ions was calculated according to formula (1). The results are shown in Figure 2 As shown, the results show that when the IDA concentration is 0.5mM and the metal ion is Ni 2+ When , the covalent immobilization efficiency of Ni-EFMMS on His-nNOS was the highest.

[0049]

[0050] Among them C a and C b are the initial His-nNOS protein concentration before immobilization and the protein concentration in the supernatant after coordination immobilization, respectively.

[0051] The hysteresis loop experimental results of Ni-EFMMS@nNOS-PSD95 composite material are shown in Figure 3 As shown, the results show that the saturation magnetization of Fe3O4, Fe3O4@nSiO2, epoxy-functionalized fluorescent magnetic mesoporous silicon, Ni-EFMMS, Ni-EFMMS@nNOS and Ni-EFMMS@nNOS-PSD95 are 69.09, 52.88, 23.54, 22.51, 22.07 and 21.34emu / g, respectively. The decrease of magnetism during the synthesis process proves the successful coating of nano-silicon layer and mesoporous silicon layer. The weak magnetic changes of Ni-EFMMS, Ni-EFMMS@nNOS and Ni-EFMMS@nNOS-PSD95 indicate that material modification and protein fixation do not significantly reduce the magnetism of the material. Under the action of magnetism, Ni-EFMMS@nNOS-PSD95 can be enriched and separated by a magnet within 30s, and can be quickly dispersed after a slight shaking, which is conducive to the recovery and reuse of the material.

[0052] Uncoupling linear assay experiments

[0053] Ni-EFMMS@nNOS-PSD95 was added to solutions of different natural active ingredients at the same concentration and shaken at 125 rpm for 5 h at 4 °C. After magnetic separation, the ratio fluorescence intensity of Ni-EFMMS@nNOS-PSD95 was measured to evaluate the decoupling efficiency of the natural active ingredients:

[0054] Taking the classic nNOS-PSD95 uncoupler ZL006 as an example, 3 mg Ni-EFMMS@nNOS-PSD95 was dispersed in 0, 0.25, 0.5, 1, 1.5, 2, and 4 mM ZL006, respectively, and shaken at 125 rpm for 5 h at 4 °C. After magnetic separation, the ratio fluorescence intensity F of Ni-EFMMS@nNOS-PSD95 was measured. 506 / F 632 The decoupling efficiency of ZL006 was calculated according to formula (3), and the F 506 / F 632 There was a linear relationship between the uncoupling efficiency and the concentration of ZL006.

[0055]

[0056] Where F 506 and F 632The fluorescence of Ni-EFMMS@nNOS-PSD95 measured at 506 nm and 632 nm, respectively.

[0057]

[0058] Where RF0 is the ratio fluorescence after the interaction between Ni-EFMMS@nNOS-PSD95 and 0 mM ZL006, RF c is the ratiometric fluorescence after the interaction between Ni-EFMMS@nNOS-PSD95 and ZL006 at c concentration, RF Blank is the ratiometric fluorescence of Ni-EFMMS@PSD95 without nNOS.

[0059] from Figure 4 It can be seen that when the concentration of ZL006 is in the range of 0.25-4 mM, the ratio fluorescence intensity is inversely proportional to the concentration of ZL006, and the uncoupling efficiency is proportional to the concentration of ZL006. It is proved that under the action of unknown uncouplers, the change in the ratio fluorescence intensity of Ni-EFMMS@nNOS-PSD95 can reasonably reflect the uncoupling efficiency of the compound, providing a new method for the screening of potential nNOS-PSD95 uncouplers in natural active ingredients.

[0060] The multifunctional epoxy carrier Ni-EFMMS was uniformly dispersed in 300 μL His-nNOS protein solution (1 mg / mL), fixed at room temperature for 24 h, and then magnetically separated. The material was uniformly dispersed in 300 μL imidazole solution and glycine solution (both 0.5 M), and incubated at 4°C for 2 h. The magnetic separation material and the supernatant were separated. The covalent protein loading rate of Example 1 was calculated using formula (1). The results showed that the covalent protein loading rate of Example 1 for His-nNOS was as high as 64% ( Figure 5 ).

[0061] Example 2

[0062] Preparation of materials:

[0063] (1) Preparation of silanized carbon dots: According to the proportion, 1 g of citric acid and 2 g of urea were added to 10 mL of formic acid and subjected to solvent thermal treatment at 160 °C for 4 h. The 10 ml dark red-brown solution obtained after solvent thermal treatment was precipitated with ethanol to obtain red carbon dots. It was dispersed in 2 mL of dimethyl sulfoxide, and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide were added for activation for 30 min, and then 5 μL of 3-aminopropyltriethoxysilane was added and shaken at room temperature for 12 h to obtain silanized carbon dots, which were stored at 4 °C for future use;

[0064] (2) Preparation of epoxy-functionalized fluorescent magnetic mesoporous silica: 60-100 mL of ultrapure water were added to the reaction vessel in proportion, and 5-20 mmol of FeCl2·4H2O and 10-40 mmol of FeCl3·6H2O were added under nitrogen protection. When the oil bath was heated to 60-120°C, 5-20 mL of ammonia water was added dropwise, and the reaction was continued for 0.5-2 h. Then, 1-4 mL of polyethylene glycol 200 was added under stirring and the reaction was continued for 5-20 min. Nitrogen was used for protection throughout the reaction. The product was magnetically separated and washed with deionized water until neutral to obtain Fe3O4 nanoparticles, which were vacuum dried at 50°C and set aside. 0.1 g of the obtained Fe3O4 was ultrasonically dispersed in a mixed solution of 80 mL of ethanol and 20 mL of deionized water, and 1 mL of ammonia water was added. After stirring, 100 μL of tetraethyl orthosilicate was slowly added dropwise. The reaction was continued at room temperature for 6 h. The product was magnetically separated and washed with deionized water until neutral to obtain Fe3O4@nSiO2. Fe3O4@nSiO2 was redispersed in a mixed solvent of 80mL deionized water, 60mL ethanol, and 1mL ammonia water, and the template agent hexadecyltrimethylammonium bromide was added to react at room temperature for 30min, and then the silanized carbon dots and 400μL tetraethyl orthosilicate were added. After reacting at room temperature for 6h, the two were co-condensed to form fluorescent magnetic mesoporous silica. The product was dispersed in acetone, refluxed at 80℃ for 2d, repeated twice, and the product was magnetically collected and vacuum dried at 45℃ to constant weight to obtain fluorescent magnetic mesoporous silica. The above 0.1g fluorescent magnetic mesoporous silica was ultrasonically dispersed in 50mL toluene, and 60μL triethylamine (Et3N) and 400μL GPTMS were slowly added dropwise. The mixture was refluxed at 115℃ for 3h under N2 protection, and the product was magnetically separated and collected. The residue was washed with toluene and methanol to remove the residue, and vacuum dried at 45℃ to constant weight to obtain epoxy functional fluorescent magnetic mesoporous silica.

[0065] (3) Preparation of multifunctional epoxy carrier Ni-EFMMS: 0.1 g epoxy functionalized fluorescent magnetic mesoporous silica was mixed with 10 mL 0.5 mM iminodiacetic acid and reacted at room temperature for 1 h. After washing with deionized water, the product was collected and continued to react with excess Ni 2+ The solution was reacted at room temperature for 2 h, and the product was collected magnetically after washing with deionized water and dried in vacuo at 45 °C to constant weight to obtain Ni-EFMMS;

[0066] (4) Preparation of Ni-EFMMS@nNOS: 3 mg of the above Ni-EFMMS was uniformly dispersed in 300 μL of His-nNOS protein solution (1 mg / mL), fixed at room temperature for 24 h, and then magnetically separated. The material was uniformly dispersed in 300 μL of imidazole solution and glycine solution (both 0.5 M), and incubated at 4°C for 2 h, respectively, and then magnetically separated.

[0067] (5) Preparation of Ni-EFMMS@nNOS-PSD95 composite material: 3 mg Ni-EFMMS@nNOS was evenly dispersed in 300 μL GFP-PSD95 (1 mg / mL) protein solution, incubated at 4°C, 175 rpm for 12 h, and magnetically separated to obtain the composite material.

[0068] Application: Ni-EFMMS@nNOS-PSD95 was added to solutions of different natural active ingredients at the same concentration and shaken at 125 rpm for 5 h at 4°C. After magnetic separation, the ratio fluorescence intensity of Ni-EFMMS@nNOS-PSD95 was measured to evaluate the decoupling efficiency of the natural active ingredients.

[0069] Example 3

[0070] Preparation of materials:

[0071] (1) Preparation of silanized carbon dots: According to the proportion, 1 g of citric acid and 2 g of urea were added to 10 mL of formic acid and subjected to solvent thermal treatment at 160 °C for 4 h. The 10 ml dark red-brown solution obtained after solvent thermal treatment was precipitated with ethanol to obtain red carbon dots. It was dispersed in 2 mL of dimethyl sulfoxide, and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide were added for activation for 30 min, and then 5 μL of 3-aminopropyltriethoxysilane was added and shaken at room temperature for 12 h to obtain silanized carbon dots, which were stored at 4 °C for future use;

[0072] (2) Preparation of epoxy-functionalized fluorescent magnetic mesoporous silica: 60-100 mL of ultrapure water were added to the reaction vessel in proportion, and 5-20 mmol of FeCl2·4H2O and 10-40 mmol of FeCl3·6H2O were added under nitrogen protection. When the oil bath was heated to 60-120°C, 5-20 mL of ammonia water was added dropwise, and the reaction was continued for 0.5-2 h. Then, 1-4 mL of polyethylene glycol 200 was added under stirring and the reaction was continued for 5-20 min. Nitrogen was used for protection throughout the reaction. The product was magnetically separated and washed with deionized water until neutral to obtain Fe3O4 nanoparticles, which were vacuum dried at 50°C and set aside. 0.1 g of the obtained Fe3O4 was ultrasonically dispersed in a mixed solution of 80 mL of ethanol and 20 mL of deionized water, and 1 mL of ammonia water was added. After stirring, 100 μL of tetraethyl orthosilicate was slowly added dropwise. The reaction was continued at room temperature for 6 h. The product was magnetically separated and washed with deionized water until neutral to obtain Fe3O4@nSiO2. Fe3O4@nSiO2 was redispersed in a mixed solvent of 80mL deionized water, 60mL ethanol, and 1mL ammonia water, and the template agent hexadecyltrimethylammonium bromide was added to react at room temperature for 30min, and then the silanized carbon dots and 400μL tetraethyl orthosilicate were added. The two were co-condensed to form fluorescent magnetic mesoporous silicon. The product was dispersed in acetone, refluxed at 80℃ for 2d, repeated twice, and the product was magnetically collected and vacuum dried at 45℃ to constant weight to obtain fluorescent magnetic mesoporous silicon. The above 0.1g fluorescent magnetic mesoporous silicon was ultrasonically dispersed in 50mL toluene, and 400μL APTES was slowly added dropwise. The mixture was refluxed at 80℃ for 12h under nitrogen protection, and the product was magnetically separated and collected. The residue was washed with toluene and methanol, and vacuum dried at 45℃ to constant weight to obtain amino-functionalized fluorescent magnetic mesoporous silicon. Weigh 0.1g of amino-functionalized fluorescent magnetic mesoporous silica, evenly disperse it in 30mL of methanol, slowly drop 0.4mmol of epichlorohydrin, stir at 50℃ for 4h, then slowly drop 0.18mmol of NaOH, and continue to react for 1h. After the reaction, separate the product magnetically, wash with methanol and deionized water, and vacuum dry at 45℃ to constant weight to obtain epoxy-functionalized fluorescent magnetic mesoporous silica.

[0073] (3) Preparation of multifunctional epoxy carrier Ni-EFMMS: 0.1 g epoxy functionalized fluorescent magnetic mesoporous silica was mixed with 10 mL 0.5 mM iminodiacetic acid and reacted at room temperature for 1 h. After washing with deionized water, the product was collected and continued to react with excess Ni 2+ The solution was reacted at room temperature for 2 h, and the product was collected magnetically after washing with deionized water and dried in vacuo at 45 °C to constant weight to obtain Ni-EFMMS;

[0074] (4) Preparation of Ni-EFMMS@nNOS: 3 mg of the above Ni-EFMMS was uniformly dispersed in 300 μL of His-nNOS protein solution (1 mg / mL), fixed at room temperature for 24 h, and then magnetically separated. The material was uniformly dispersed in 300 μL of imidazole solution and glycine solution (both 0.5 M), and incubated at 4°C for 2 h, respectively, and then magnetically separated.

[0075] (5) Preparation of Ni-EFMMS@nNOS-PSD95 composite material: 3 mg Ni-EFMMS@nNOS was evenly dispersed in 300 μL GFP-PSD95 (1 mg / mL) protein solution, incubated at 4°C, 175 rpm for 12 h, and magnetically separated to obtain the composite material.

[0076] Application: Ni-EFMMS@nNOS-PSD95 was added to solutions of different natural active ingredients at the same concentration and shaken at 125 rpm for 5 h at 4°C. After magnetic separation, the ratio fluorescence intensity of Ni-EFMMS@nNOS-PSD95 was measured to evaluate the decoupling efficiency of the natural active ingredients.

[0077] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A ratio fluorescent magnetic composite material, characterized in that: The ratio fluorescent magnetic composite material comprises epoxy functional fluorescent magnetic mesoporous silicon, metal ions, His-nNOS and GFP-PSD95. The ratio fluorescent magnetic composite material uses epoxy functional fluorescent magnetic mesoporous silicon as a carrier, carries metal ions, and fixes His-nNOS on the surface of the material. GFP-PSD95 is combined with His-nNOS on the surface to be fixed to obtain the ratiometric fluorescent magnetic composite material; Preferably, the metal ion is selected from iron, cobalt, copper, nickel or zinc.

2. The ratiometric fluorescent magnetic composite material according to claim 1, characterized in that: In the ratio fluorescent magnetic composite material, the mass ratio of epoxy functionalized fluorescent magnetic mesoporous silicon, metal ions, His-nNOS and GFP-PSD95 is 10:0.09:1:

1.

3. The method for preparing the ratio fluorescent magnetic composite material according to claim 1, characterized in that: The method comprises the following steps: (1) Preparation of silylated carbon dots: citric acid and urea are added to formic acid to perform solvent thermal treatment, and the solvent thermal treatment product is precipitated by ethanol to obtain red carbon dots; the red carbon dots are dispersed in dimethyl sulfoxide, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide are added for activation, and 3-aminopropyltriethoxysilane is added, and the mixture is shaken at room temperature to obtain the silylated carbon dots; (2) Preparation of epoxy-functionalized fluorescent magnetic mesoporous silica: Fe3O4 magnetic nanoparticles were acoustically dispersed in an 80% ethanol aqueous solution, ammonia water was added, tetraethyl orthosilicate was slowly added dropwise after stirring evenly, and the suspension was reacted at room temperature until the color of the suspension became lighter, gradually changing from black to brown. The product was magnetically separated and washed with deionized water until neutral to obtain Fe3O4@nSiO2; Fe3O4@nSiO2 was redispersed in a mixed solvent of water, ethanol and ammonia water, and a template was added to react at room temperature until the template was evenly dispersed in the mixed solvent; Add the silanized carbon dots obtained in step (1), and add tetraethyl orthosilicate for the second time, the silanized carbon dots and tetraethyl orthosilicate are co-condensed on the surface of Fe3O4@nSiO2 to form fluorescent magnetic mesoporous silicon, mechanically stir until the silanized carbon dots and tetraethyl orthosilicate are condensed to form a mesoporous silicon layer, add 3-glycidyloxypropyltrimethoxysilane for epoxy functionalization, continue to stir the reaction, disperse the product in acetone, reflux, repeat twice, collect the product magnetically, and vacuum dry to constant weight to obtain epoxy-functionalized fluorescent magnetic mesoporous silicon; (3) Preparation of a multifunctional epoxy carrier: The epoxy-functionalized fluorescent magnetic mesoporous silica obtained in step (2) is mixed with water or an aqueous solution of iminodiacetic acid, and reacted at room temperature until the iminodiacetic acid fully reacts with the epoxy group; after washing with deionized water, the product is collected and continued to react with an excess metal ion solution at room temperature until the carboxyl group fully chelates the metal ion; after washing with deionized water, the product is magnetically collected and vacuum dried to constant weight to obtain a multifunctional epoxy carrier; (4) Preparation of nNOS-fixed epoxy-functionalized fluorescent magnetic mesoporous silica: The multifunctional epoxy carrier prepared in step (3) is uniformly dispersed in a His-nNOS protein solution, fixed at room temperature, and then magnetically separated. The separated material is incubated in an imidazole solution and a glycine solution in turn, and then magnetically separated to obtain the epoxy-functionalized fluorescent magnetic mesoporous silica; (5) Preparation of ratiometric fluorescent magnetic composite material: The nNOS-fixed epoxy-functionalized fluorescent magnetic mesoporous silica prepared in step (4) is uniformly dispersed in the GFP-PSD95 protein solution, incubated, and magnetically separated to obtain the ratiometric fluorescent magnetic composite material.

4. The preparation method according to claim 3, characterized in that: The mass ratio of citric acid to urea in step (1) is 1:1 to 1:3, and the concentration of citric acid in formic acid is 0.1 g / mL; the solvent thermal treatment is performed at 160° C. for 4 h; The molar ratio of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride to N-hydroxysuccinimide is 1:1-1:2, and the molar ratio of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride to 3-aminopropyltriethoxysilane is 1:0.1-1:0.

3.

5. The preparation method according to claim 3, characterized in that: Step (2) The concentration of the Fe3O4 magnetic nanoparticles in the 80% ethanol aqueous solution is 1 mg / ml, the volume ratio of the 80% ethanol aqueous solution to ammonia water is 100:1, and the volume ratio of tetraethyl orthosilicate to ammonia water is 1:10; the volume ratio of water, ethanol and ammonia water in the mixed solvent is 80:60:1; the concentration of the Fe3O4@nSiO2 in the mixed solvent is 0.5-1 mg / mL; the template is hexadecyltrimethylammonium bromide, and the mass ratio of Fe3O4@nSiO2 to the template is 1:3-1:5; the mass ratio of the silanized carbon dots to tetraethyl orthosilicate is 1:60-1:90; the mechanical stirring condition is 750 r / min; the molar ratio of the tetraethyl orthosilicate added for the second time to 3-glycidyloxypropyltrimethoxysilane is 2:1-6:

1.

6. The preparation method according to claim 3, characterized in that: The concentration of the epoxy-functionalized fluorescent magnetic mesoporous silicon in the step (3) is 0.01 g / mL; the concentration of the aqueous solution of iminodiacetic acid is not higher than 50 mM; the metal ion is iron, cobalt, copper, nickel or zinc; The vacuum drying temperature is 45°C.

7. The preparation method according to claim 3, characterized in that: In step (4), the mass ratio of the multifunctional epoxy carrier to His-nNOS is 20:1 to 1:1, and the fixation time at room temperature is 12 to 36 hours; the concentrations of the imidazole solution and the glycine solution are both 0.5 M; and the incubation condition is 4° C. for 2 hours.

8. The preparation method according to claim 3, characterized in that: The incubation conditions in step (5) are 4° C. and 175 rpm for 12 h, and the mass ratio of nNOS and PSD95 used in protein fixation is 0.5:1 to 2:

1.

9. Use of the ratiometric fluorescent magnetic composite material according to claim 1 in screening potential anti-stroke active ingredients of natural medicines.

10. The use according to claim 9, characterized in that: The ratio fluorescence magnetic composite material is added to the natural medicine to be screened or the solution of the active ingredient of the natural medicine, and then magnetically separated after shaking. The ratio fluorescence intensity of the ratio fluorescence magnetic composite material is measured, and the active ingredients of the natural medicine that meet the conditions can be compared and screened.

Citation Information

Patent Citations

  • A magnetic composite material, its preparation method and application

    CN114192117B